1994
DOI: 10.7589/0090-3558-30.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Infection of Columbian Black-Tailed Deer With the Lyme Disease Spirochete

Abstract: The course of Borrelia burgdorferi-infection in Columbian black-tailed deer. (Odocoileus hemionus columbianus), its effect on the health of these animals, and their reservoir competence for fleas were evaluated experimentally. Four yearling females inoculated intramuscularly with 10(8) organisms of the CA4 strain of B. burgdorferi, and two yearling males unexposed to spirochetes, were monitored daily for 3 mo. Spirochetes were reisolated from the blood of three does at 14 or 70 days postinjection, and from sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Borrelia burgdorferi sensu lato is a zoonotic pathogen whose natural infectious cycle alternates between a tick vector and rodent or bird reservoir hosts (1,7,8,14,32,33,36). Transmission of B. burgdorferi to humans occurs through the bite of an infected tick and can lead to Lyme disease, which is a major public health concern in areas of North America and Europe where B. burgdorferi is endemic (8,53).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Borrelia burgdorferi sensu lato is a zoonotic pathogen whose natural infectious cycle alternates between a tick vector and rodent or bird reservoir hosts (1,7,8,14,32,33,36). Transmission of B. burgdorferi to humans occurs through the bite of an infected tick and can lead to Lyme disease, which is a major public health concern in areas of North America and Europe where B. burgdorferi is endemic (8,53).…”
mentioning
confidence: 99%
“…Our findings have basic implications for horizontal gene transfer among B. burgdorferi strains with distinct plasmid contents. Further characterization and identification of the nucleotide sequences recognized by BBE02 and BBQ67 will facilitate efficient genetic manipulation of this pathogenic spirochete.Borrelia burgdorferi sensu lato is a zoonotic pathogen whose natural infectious cycle alternates between a tick vector and rodent or bird reservoir hosts (1,7,8,14,32,33,36). Transmission of B. burgdorferi to humans occurs through the bite of an infected tick and can lead to Lyme disease, which is a major public health concern in areas of North America and Europe where B. burgdorferi is endemic (8, 53).…”
mentioning
confidence: 99%
“…This bacterium survives in a complex enzootic cycle transmitted by Ixodes ticks and infects a wide range of vertebrate hosts (4)(5)(6)(7)(8). B. burgdorferi must adapt to markedly different environments within the arthropod vector and mammalian host to ensure successful colonization, persistence, and transmission throughout the natural infectious cycle.…”
mentioning
confidence: 99%
“…In northwestern California, studies on naturally and experimentally infected duskyfooted wood rats (Neotoma fuscipes), deer mice (Peromyscus maniculatus), and Columbian black-tailed deer (Odocoileus hemionus columbianus) revealed that animals infected via needle inoculation or tick feeding did not develop clinical manifestations consistent with Lyme disease Lane 1994, Lane et al 1994). Experimental infections of mice with human isolates in the northeastern United States indicated strain differences in fitness, pathogenicity, and ability to disseminate (Wang et al 2001, Haninková et al 2008.…”
Section: Introductionmentioning
confidence: 99%